(untitled) (Bangladesh Journal of Pharmacology, 2017)
Transmission electron microscopy (TEM) has a profound impact on knowledge and understanding of bacteria and other microbial populations. The 1000-fold improvement in resolution provided by TEM has allowed visualization of bacterial cells. Of all the types of microscopy exploited to date, TEM is the one with the most advantageous resolution limit and therefore it is a very efficient technique for deciphering the cell architecture and relating it to function. This visual experiment aims to provide an overview of the most important technique, TEM that we can apply to a biological sample, tissue or cells, to observe it with an internal structure, from the most conventional to the latest generation. Processes and concepts are defined, and the advantages and disadvantages of the TEM technique are assessed along with the image and information that we can obtain by using each one of them. Video Clips of Methodology: Sample preparation: coating, staining and critical drying: 4 min 36 sec Full Screen Alternate TEM instrumentation and image analysis: 4 min 37 sec Full Screen Alternate